The Effect of Solvability, Profitability, and Macroeconomics on Stock Price Growth on Automotive Sub Sector Companies Listed on IDX - Suhartono, Suhartono; Khairani Aulia (Green Publisher, 2023)
The purpose of this study is to provide empirical evidence about the effect of solvability, profitability, and macroeconomics on the stock price growth for automotive sub-sector companies listed on the IDX for the 2019-2021 period. Solvability is proxied using the debt to equity ratio, profitability is proxied using earning per share. The macroeconomics is represented exchange rate growth and interest rates. The data analysis technique used in this study is multiple linear regression analysis. The population in this study are automotive sub-sector companies on the IDX for the 2019-2021 period, which consists of 12 companies. Determination of the sample using saturated sampling with a total of 36 samples. The results showed that partially debt to equity ratio and exchange rate growth had a positive and not significant effect on stock price growth, earning per share had a positive and significant effect on stock price growth, and interest rate had a negative effect and not significant effect on stock price growth.